The attrition rate of vocabulary among EFL learners across different proficiency levels - Asgari, Azadeh; Mustapha, Ghazali (Universiti Putra Malaysia Press, 2012)
This study aimed to investigate the attrition rate of EFL concrete and abstract vocabulary among continuing and non-continuing Iranian female and male English language learners across different proficiency levels. They were students of a University who majored in different fields (between 20 and 25 years old). There was no treatment involved in this study, where the researcher compared two groups using the same variables. Hence, the design of the current study is an ex-post facto design. A 40-item vocabulary test, which varied across two proficiency levels, was used to measure the rate of vocabulary attrition as the instrument of this research. In the two stages, after an interval of three months, the students were requested to take the same tests. The results revealed that there was no significant difference between the EFL attrition rate of the abstract and concrete nouns among the continuing students across different proficiency levels. However, this hypothesis was rejected for the non-continuing learners at intermediate and advanced proficiency levels.